2018
DOI: 10.21037/tau.2018.01.06
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant androgen deprivation therapy for prostate cancer treated with radiation therapy

Abstract: Radiation therapy is a commonly used curative modality for prostate cancer. The addition of androgen deprivation therapy (ADT) increases the curative potential of prostate radiotherapy (RT) in multiple subsets of patients. In addition to having an independent cytotoxic effect, current evidence suggests that androgen deprivation synergistically works with radiation therapy by preventing DNA repair. Given the wide-ranging toxicities of this therapy, clinicians must judiciously choose which patients may benefit f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 72 publications
1
22
0
Order By: Relevance
“…Alternatively, an enhanced immune response has been suggested as another possible mechanism of the synergistic effect of AdT and RT (15,16). Despite these benefits, treatment with ADT can result in a multitude of iatrogenic conditions including increased risk for diabetes, cardiovascular diseases, sexual health dysfunction, depression, cognitive and mood dysfunction (11,17). These treatment-related conditions can greatly reduce health-related quality of life (18).…”
Section: Cancer-related Fatigue During Combined Treatment Of Androgenmentioning
confidence: 99%
“…Alternatively, an enhanced immune response has been suggested as another possible mechanism of the synergistic effect of AdT and RT (15,16). Despite these benefits, treatment with ADT can result in a multitude of iatrogenic conditions including increased risk for diabetes, cardiovascular diseases, sexual health dysfunction, depression, cognitive and mood dysfunction (11,17). These treatment-related conditions can greatly reduce health-related quality of life (18).…”
Section: Cancer-related Fatigue During Combined Treatment Of Androgenmentioning
confidence: 99%
“…Results of the OABSS questionnaire indicated that the majority of patients (88%) had mild urinary symptoms with an average value of 3.2 (range, 1-5). According to the IPSS questionnaire, 27% of patients had mild symptoms with an average score of 5 (range, 4-6), and the majority of patients (62%) demonstrated moderate symptoms with an average score of 12.8 (range, [8][9][10][11][12][13][14][15][16][17][18][19]. There was no statistically significant difference between 18 Gy and 21 Gy arms, except in baseline quality of life, which included more patients who answered "delighted" in 18 Gy arm.…”
Section: Resultsmentioning
confidence: 99%
“…Most patients enrolled in the present study received ADT over 1 year. Usual recovery of testosterone occurs slowly over 1–2 years [ 16 ]. The median follow-up time of 35 months (range of 19 to 43 months) is insufficient to determine the exact long-term tumor control rate after testosterone recovery.…”
Section: Resultsmentioning
confidence: 99%
“…Presence of lymph-node (LN) metastasis in patients with PC undergoing radical prostatectomy (RP) is the strongest risk factor for both, tumor recurrence and cancer-specific mortality [2,3]. In patients with LN-positive PC, adjuvant treatment after RP with either androgen-deprivation therapy (ADT) alone or ADT in combination with pelvic radiation therapy (RT) has shown a benefit in overall survival (OS), cancer-specific survival (CSS), and progression-free survival (PFS) [4][5][6][7]. LN staging is crucial to assign node-positive patients to adjuvant treatment and thereby prolong CSS in these patients [8,9].…”
Section: Introductionmentioning
confidence: 99%